The European External Action Service. Progress or Regress in the Political Integration of Europe? (Economic and Political Thought, 2012)
The article aims to analyze the European Union diplomacy, i.e. theEuropean External Action Service (EEAS), which was created based onthe decisions of the Treaty of Lisbon. The article presents such issues as thetheoretical difference between foreign policy and diplomacy, which are oftenconfused in journalistic texts, the origin of the EU’s foreign service, and thedefinition of its character and basic tasks. The article also contains a discussionof the role the EEAS plays in the Common Security and Defence Policy.The article also deals with the EEAS inter-institutional location, which isvery important from the point of view of its daily functioning. The articleends with some deliberations in connection with the role of the High Representativefor Foreign Affairs and Security Policy as well as the role of themember states in the current functioning of the European External Action Service.